DIGITALIZATION AND E-COMMERCE OF MICRO, SMALL AND MEDIUM ENTERPRISES ACEH SOUVENIRS IN MUARA BATU DISTRICT, NORTH ACEH REGENCY - Murniati; Cut Sukmawati; Ti Aisyah; Aiyub; Nazaruddin; Grace Shella Karisma; Atikah Rifki (RADJA PUBLIKA, 2024)
Community service activities are carried out in Muara Batu District, North Aceh Regency. The determination of this location is based on several reasons, including the existence of Muara Batu District in the Malikussaleh University campus area which is directly adjacent to immigrants from students and people who work around the area, besides that, the main thing is that in Muara Batu District, North Aceh Regency, there are many Acehnese souvenir craftsmen who are still very behind in marketing their products so that craftsmen find it very difficult to achieve maximum sales achievement levels and this can result in production stalls which can have an effect on closing their businesses. The method of implementing community service is carried out with stages of preparation, training and mentoring as well as Monitoring and evaluation of activities, where we will monitor the craftsmen whether they have maximized their use of digital media in the process of selling their products. To facilitate the monitoring or evaluation process, the activity implementation team has also formed a WashUp group, where in the group the implementation team and the coaching team will interact and communicate with each other about matters relating to methods, strategies or matters relating to how to digitize the sale of Acehnese souvenir products. This activity was attended by UMKM craftsmen of Acehnese souvenirs, namely from Ule Madon Village, Meunasah Aron Village and Mane Tunoeng Village and craftsmen of other products as well, the Sub-district Head and also staff at the Sub-district Head's office, Mura Batu District, North Aceh Regency.